PERAN DANA PIHAK KETIGA DALAM KINERJA LEMBAGA PEMBIAYAAN SYARIAH DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA - Fitri, Maltuf (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2016)
The development of the performance syariah financing institutions in Indonesia keeps increased positive this can be seen of the total assets and third party funds (DPK) that increase over a period of years 2010-2014. During the period of the year the ratio DPK to the total assets of syariah financing institutions reached 78 percent.The indicated that the role DPK for these very strategic performance and the funding institution banking business. In this paper the tried to explain the role of third party funds in an institution syariah funding as an element the certaintly in the provison of financing and as an element that influences the performance business of syariah financing institutions. The importance of the role of DPK for syariah financing institutions hence need to know the factors that affect the development DPK. Approach analysis this paper is descriptive empirical who testing of theoretically and approach in empirical of studies related.